THE PERCEPTION OF THE WORSHIPERS OF MASJID GEDHE KAUMAN YOGYAKARTA ON MUI FATWA ABOUT CONGREGATIONAL PRAYERS DURING PANDEMIC - Nur Aniyah; Twediana Budi Hapsari (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2021)
The COVID-19 pandemic has an impact on various aspects of life, as well as in religious aspects. Carrying out congregational prayers at mosques during a pandemic requires strict health protocols. With the many questions from the public regarding the implementation of congregational prayers during the pandemic, MUI issued fatwa No. 31 of 2020 regarding the holding of congregational prayers to prevent transmission of the COVID-19 outbreak as a guideline. This study aims to determine the perception of the worshipers of Masjid Gedhe Kauman on MUI fatwa No. 31 of 2020 concerning congregational prayers during the pandemic and knowing whether there is a difference in perception between adult congregations (≤45 years) and elderly congregations (≥46 years). The method used was descriptive quantitative with data collection techniques using questionnaires and observations. The data analysis used was descriptive analysis and independent sample T-Test. The results show that the perception of the worshipers of the Masjid Gedhe Kauman on MUI fatwa concerning congregational prayers during the pandemic was positive, as indicated by the mean value of 3.0682. Research indicators consist of five indicators, namely indicators of giving more distance between shaf (line) during congregational prayers, using masks during prayer, implementing congregational prayers with health protocols, shortening the reading of letters during congregational prayers, and giving advice to worshipers who are sick when joining congregational prayers. The worshipers’ perception of each of the majority indicators is positive, with the highest total mean value of 3.22 on giving advice to worshipers who are sick when joining congregational prayers. Meanwhile, the Sig. t count from the independent sample T-Test is 0.9530.05, which indicates that there is no significant difference between the perceptions of adult worshipers (≤45 years) and elderly worshipers (≥46 years).